Perbandingan Performans Dua Strain Broiler yang Mengonsumsi Air Kunyit - Syahrio Tantalo (Politeknik Negeri Lampung., 2010)
The objective of the research was to know comparation of two strains of broiler performance when water kunyit of consumption. Level of water kunyit as treatmentwas 10 g/600 ml. Two strains of broiler were CP 707 unsexed and Lohmann unsexed. Every broiler strain consist of 100 Day Old Chicken (DOC). Experiment was designed with two treatments of strain broiler and each treatment had 15 replications. Each replication was 6 or 7 DOC. Comparison of data was analyzed by using t-student on signification 5% (Steel dan Torrie, 1993). Parameters measured were water consumption, feed intake, body weight gain, feed conversion, and income over feed cost. Results showed the highest effect of kunyit water significant (P<0,05) of broiler performance of strain CP 707 on water consumption, feed intake, and body weight gain, but no significant effect on feed conversion, and income over feed cost. Broiler of strain CP 707 was the responsive to treated water kunyit of consumption which shown on its effect on performance.Keywords: water kunyit, performance, strain, broiler